(untitled) (VIABEL: Jurnal Ilmiah Ilmu-Ilmu Pertanian, 2018)
Urban is the destination and center of all community activities. According to Harahap, (2013) states that each population has a significant increase and population growth. Communities living in cities are highly demanded to have high productivity in order to compete and meet their individual needs. But it cannot be denied that there are some urban communities who are not able to compete with the population. The profession of a housewife in one example is a society that is not competitive and unproductive. Based on national socio-economic survey data from the Central Bureau of Statistics (2004) stated that most mothers in cities from 40 years who have children are 63.3% of households and 29.6% of them are career women. This is because being a housewife in a city depends more on the husband’s income. Lately in Indonesia there has been considerable economic upheaval in various sectors that have enabled an increase in various needs in various regions of Indonesia. This condition requires housewives to play the brain to support family needs. Aquaverticuture insulation of agricultural development and efforts in increasing productive business of housewives is a solution that can be offered in supporting the economy, this implementation program will be implemented in the community of housewives in urban areas, while the areas to be piloted in this program are the Circle of Friends Dahlia and Gardania at Sulfate Gardens Housing, Pandanwangi Village, Blimbing, Malang City.